Vocal fold vibration amplitude, open quotient, speed quotient and their variability along glottal length: Kymographic data from normal subjects. (December 2013) - Lohscheller, Jörg; Švec, Jan G.; Döllinger, Michael
Abstract: Quantitative knowledge about healthy vocal fold vibration characteristics provides the basis for an objective assessment of vocal fold vibrations. In this study, using high-speed videolaryngoscopy the alterations of the relative vibration amplitudes, open quotients, and speed quotients were analyzed along the glottal length in 30 male and 30 female healthy subjects. The maximum vibration amplitude was identified at 41.1% ± 10.8% and 46.5% ± 18.0% of the visible glottal length in females and males, respectively. The average open quotients decreased in females and males from posterior to anterior, while the speed quotients did not change systematically. The reported normative values can be used to distinguish normal and abnormal vibrations in clinical practice when aiming at quantitative diagnosis of functional voice disorders.